Objectives of military personnel financial and legal protection under martial law - Yu. M. Kret (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the issues of financial and legal protection of servicemen as a direction of the State's financial activity under martial law. It has been determined that the financial and legal protection of servicemen is aimed at material support of the entire range of measures on social policy of the State at the expense of budgetary funds. It has been proved that the allocation and use of budget expenditures in 2023 are conditioned by the martial law in which the country is, and have a temporary content, but cover a significant amount of funds, which affected the State's ability to perform its social function.